Two-Way Fano Resonance Switch in Plasmonic Metamaterials - Zhou, Yong Jin; Dai, Li Hui; Li, Qiao Yu; Xiao, Zhong Yin (Frontiers in Physics, 2020)
A two-way Fano resonance switch in the plasmonic metamaterials has been proposed and experimentally demonstrated. The electrical Fano switch is composed of two concentric spoof localized surface plasmons (LSPs) resonators. By adjusting the slit in the inner spoof LSPs resonator, two different Fano resonance modes could be supported. By loading a Schottky barrier diode (SBD) across the slit in the inner LSPs resonator, both Fano resonance modes can be simultaneously switched when the SBD diode is forward-biased or reverse-biased and their switch status is opposite. Both simulated and measured results agree well at microwave frequencies and verify the two-way Fano resonance switch. The devices could be applied in many applications such as plasmonic circuits, multi-way sensing or switching, and so on.